Alternative and Complementary Approaches for the Treatment of Inflammatory Bowel Disease: Evidence From Cochrane Reviews. Issue 6 (27th September 2019) - Chande, Nilesh; Costello, Samuel P; Limketkai, Berkeley N; Parker, Claire E; Nguyen, Tran M; Macdonald, John K; Feagan, Brian G
Abstract : The Cochrane IBD Group presented a symposium at Digestive Diseases Week 2018 entitled "Alternative and Complementary Approaches for the Treatment of IBD: Evidence from Cochrane Reviews." This article summarizes the data presented at this symposium. Video Abstract: